PROFESSION OF BIOLOGY TEACHER IN UKRAINE: STATISTICAL CHARACTERISTICS - Lidiia Vashchenko (Borys Grinchenko Kyiv Metropolitan University, 2024)
In the context of reforming general secondary education, it is important to identify and analyze the changes occurring in the human resources of the general secondary education system under the influence of various factors, particularly the martial law in the country. This study focuses on biology teachers as an example. The following system of indicators was used to statistically characterize biology teachers in modern Ukraine: the number of teaching staff (differentiated by urban and rural areas); the age and gender structure of teachers; the structure of teaching staff by education level; the number of students per teacher; the number of biology classrooms in general secondary education institutions; and the number of institutions and students involved in specialized biology education. The article presents the results of the analysis of statistical indicators regarding biology teachers in the general secondary education system. A trend of gradual reduction in educational institutions and, accordingly, teachers, including biology teachers, was identified. Attention is drawn to the decrease in the number of biology teachers under the age of 30 (30%). Statistics indicate a high educational level among biology teachers: nearly 98% have a master's degree. The number of urban educational institutions with equipped biology classrooms is gradually increasing. Overall, the percentage of high school students involved in specialized education is gradually rising nationwide. At the same time, an analysis of statistical data on the functioning of specialized biology education suggests that over the past five years, there has been a gradual decrease in the number of students engaged in specialized biology education.